Prevalence and risk factors for Enterobacteriaceae in patients hospitalized with community‐acquired pneumonia. Issue 5 (5th August 2019) - Villafuerte, David; Aliberti, Stefano; Soni, Nilam J.; Faverio, Paola; Marcos, Pedro J.; Wunderink, Richard G.; Rodriguez, Alejandro; Sibila, Oriol; Sanz, Francisco; Martin‐Loeches, Ignacio; Menzella, Francesco; Reyes, Luis F.; et al.
ABSTRACT: Background and objective: Enterobacteriaceae (EB) spp. family is known to include potentially multidrug‐resistant (MDR) microorganisms, and remains as an important cause of community‐acquired pneumonia (CAP) associated with high mortality. The aim of this study was to determine the prevalence and specific risk factors associated with EB and MDR‐EB in a cohort of hospitalized adults with CAP. Methods: We performed a multinational, point‐prevalence study of adult patients hospitalized with CAP. MDR‐EB was defined when ≥3 antimicrobial classes were identified as non‐susceptible. Risk factors assessment was also performed for patients with EB and MDR‐EB infection. Results: Of the 3193 patients enrolled with CAP, 197 (6%) had a positive culture with EB. Fifty‐one percent ( n = 100) of EB were resistant to at least one antibiotic and 19% ( n = 38) had MDR‐EB. The most commonly EB identified were Klebsiella pneumoniae ( n = 111, 56%) and Escherichia coli ( n = 56, 28%). The risk factors that were independently associated with EB CAP were male gender, severe CAP, underweight (body mass index (BMI) < 18.5) and prior extended‐spectrum beta‐lactamase (ESBL) infection. Additionally, prior ESBL infection, being underweight, cardiovascular diseases and hospitalization in the last 12 months were independently associated with MDR‐EB CAP. Conclusion: This study of adults hospitalized with CAP found a prevalence of EB of 6% and MDR‐EB of 1.2%, respectively. The presence of specific risk factors, such as prior ESBL infection and being underweight, should raise the clinical suspicion for EB and MDR‐EB in patients hospitalized with CAP. Abstract : Hospitalized adults with community‐acquired pneumonia (CAP) have low prevalence of Enterobacteriaceae (EB, 6%) and multidrug‐resistant (MDR)‐EB (1.2%), respectively. Specific risk factors, such as prior extended‐spectrum beta‐lactamase infection and being underweight, should raise the clinical suspicion for EB and MDR‐EB in patients hospitalized with CAP. See related Editorial